1987
DOI: 10.1111/j.1365-3016.1987.tb00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Village health workers are able to teach mothers how to safely prepare sugar/salt solutions

Abstract: In the predominantly rural Hewu district of Ciskei 54% of infant deaths are diarrhoea-related. The aim of this study was to determine whether village health workers (VHWs) could teach mothers to safely prepare homemade sugar-salt solutions (SSS). VHWs from 11 villages were selected for training while 11 randomly selected villages acted as controls. VHWs selected for training were taught to prepare SSSs and to teach mothers with children under 5 years about the use of such solutions. A card illustrating the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In malaria control programs, they have been shown to be very efficient in distribution of Insecticide-impregnated Bed Nets (IBNs) in the community. In addition, CHIs have been intensively used to provide prenatal care, vaccinations, vitamins and check-ups, as well as to promote breastfeeding, oral rehydration, malaria treatment and fever management in remote areas [ 6 , 8 , 9 ]. The majority of these activities require limited diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In malaria control programs, they have been shown to be very efficient in distribution of Insecticide-impregnated Bed Nets (IBNs) in the community. In addition, CHIs have been intensively used to provide prenatal care, vaccinations, vitamins and check-ups, as well as to promote breastfeeding, oral rehydration, malaria treatment and fever management in remote areas [ 6 , 8 , 9 ]. The majority of these activities require limited diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of primary research on CHW programmes, including their governance, has been conducted in SA over several decades, making important contributions to the national and global bodies of evidence on this cadre. [44][45][46][47][48] Several systematic reviews of the global evidence have been undertaken, including on the effectiveness of this cadre in improving child and adult health outcomes [49][50][51] and on key barriers and facilitators to the An ecosystem for health systems evidence…”
Section: The Roles Of Health Policy and Systems Researchmentioning
confidence: 99%
“…Vi-llage health workers have been employed in the control of EVD outbreak in Uganda [54]. In South Africa, VHWs were trained on how to make sugar salt solutions and they were able to successfully teach mothers to prepare them [55]. In Gambia, a longitudinal study on the impact of introduction of village health workers showed that the infant and child mortality rate had reduced [56].…”
Section: Studies On the Role And Impact Of Village Health Workers In mentioning
confidence: 99%